Productivity and preference of salt tolerant Boro rice varieties in saline non-gher and gher ecosystems (Bangladesh Rice Journal, 2015)
Use of marginal coastal saline lands for rice cultivation is one of the options to sustain the net rice cropped area and rice production. On-farm farmers participatory field trial was conducted in Bangladesh during 2012 and 2013 in non-gher and gher of medium saline ecosystems. The objective of the study was to identify suitable Boro variety for medium saline soils. Salt tolerant rice varieties, BRRI dhan47 and Binadhan-8 were evaluated along with widely adopted BRRI dhan28 in non-gher area. BRRI dha47, Binadhan-8 and Binadhan-10 were tested in saline ghers. Crops were irrigated with water of 1.89 to 3.5 dS m-1 at different growth stages respectively. In saline non-gher, where soil salinity went up to 6.35 dS m-1, the highest grain yield was produced by Binadhan-8 (4.57 t ha-1) followed by BRRI dhan28 (4.23 t ha-1). The highest grain yield was recorded in Binadhan-10 (5.14 t ha-1) in ghers which was 6 and 12% higher than BRRI dhan47 and Binadhan-8 respectively at soil salinity of 7.43 dS m-1. Farmers preferred Binadhan-10 as a salt tolerant variety for its higher grain yield and medium grain quality.Bangladesh Rice j. 2014, 18(1&2): 18-23